LES‐VOF Simulation and POD Analysis of the Gas‐Jet Wiping Process in Continuous Galvanizing Lines. Issue 2 (9th November 2017) - Eßl, Werner; Pfeiler, Claudia; Reiss, Georg; Ecker, Werner; Riener, Christian K.; Angeli, Gerhard
Abstract : Gas‐Jet wiping is a widely applied technology in continuous galvanizing mills, which enables the adjustment of the specific coating mass by an impinging turbulent gas‐jet. The unsteady impingement conditions, however, are reported to cause surface non‐uniformities such as waves. In this study, proper orthogonal decomposition (POD) is used to analyze an industrial gas‐jet wiping process. POD allows to objectively extract the most dominant flow structures (modes) and their dynamics from the impinging jet. The acquisition of the necessary temporally and spatially highly resolved flow data is done by a LES‐VOF simulation model. The POD analysis shows that jet flapping and axial fluctuations of the jet core are the most dominant spatial modes in the studied case. The frequency range of the modes as well as the frequency range of the height fluctuations of the impinged film are compared in a spectral analysis. Additionally, it is shown that slight changes, for example, the absence of the thin liquid film on the impinged surface, alters the frequency range of the dominant POD modes, whereas the modes themselves remain mostly unchanged. Abstract : This paper presents an objective analysis of the gas‐jet wiping process, as it is used in continuous galvanizing mills. In gas‐jet wiping, the impinging jet displays an unsteady behavior which can give rise to the formation of surface waves on the coating. The prevailing unsteady flow structures are extracted with POD, spectrally analyzed, and compared to the film dynamics.